Shining light on drug discovery: optogenetic screening for TopBP1 biomolecular condensate inhibitors - Morano, Laura; Vie, Nadia; Aissanou, Adam; Hodroj, Dana; Garambois, Véronique; Fauvre, Alexandra; Promonet, Alexy; Egger, Tom; Bordignon, Benoît; Hassen-Khodja, Cédric; Fiachetti, Solène; Basbous, Jihane; et al. (NAR cancer, 2025)
Abstract Human topoisomerase IIβ binding protein 1 (TopBP1) is a scaffold protein involved in DNA replication initiation, DNA repair, transcription regulation, and checkpoint activation. TopBP1 forms nuclear condensates that act as a molecular switch to amplify ATR activity and promote the activation of the checkpoint effector kinase Chk1. In cancer cells, ATR activity is crucial to tolerate the intrinsically high level of DNA lesions and obstacles that block replication fork progression. Thus, ATR inhibitors are currently tested in clinical trials, often in combination with chemotherapy drugs. However, resistance and toxicity are still major issues. The weak interactions that hold TopBP1 condensates together are highly sensitive to changes in the cellular milieu, suggesting that small molecules may alter the formation of TopBP1 condensates. Here, we developed a high-throughput screening system to identify TopBP1 condensation modulators. This system allowed us to identify FDA-approved drugs, including thimerosal and quinacrine, that inhibit TopBP1 condensation and block the activation of ATR/Chk1 signaling. Mechanistically, quinacrine impaired TopBP1’s ability to associate with chromatin, thereby interfering with its capacity to form condensates. Furthermore, quinacrine enhanced the therapeutic efficacy of 5-fluorouracil and irinotecan, components of the clinically used FOLFIRI regimen in a mouse model of peritoneal carcinomatosis from colorectal cancer. Graphical Abstract Graphical Abstract